Avaliação da paisagem de bacias hidrográficas e sua influência sobre parâmetros ambientais e comunidades de peixes de tributários do Baixo Rio Iguaçu - Celestino, Elaine Fernandes (2019)
The continuous environmental degradation is a reality all over the world, bringing drastic changes in the landscape due to anthropic actions, especially linked to the growth of urban centers, agricultural expansion and energy generation. In Brazil the Mata Atlântica is the biome most impacted Brazilian and represents one of the largest hotspots in the world. In the state of Paraná, this pattern of degradation is no different. Knowing the dimension of these impacts is necessary to define conservation practices. In this scenario, the objective of this study was to evaluate the effects of degradation of the Iguaçu River basins in relation to: i) environmental fragility, ii) connectivity and conservation of riparian corridors, iii) environmental parameters, and iv) populational attributes of the fish. For this we used multivariables such as the use of the soil that was evaluated with geoprocessing of images and in situ evaluations with application of Rapid Assessment Protocol (PAR), slope, soil classification and rainfall. This was necessary to help understand the conservation of natural areas and the segregation of the watershed in Agrarian (AGR) and Florested (FLO). We verified that the watersheds are heterogeneous mosaic of the landscape, with predominance of agricultural activities, submitted to the average environmental fragility. Riparian corridors do not have the size required by legislation, riparian areas are fragmented and contain exotic species. We propose that a multi-factorial approach be used to evaluate waterhed to reduce sampling errors and to demonstrate the actual state of conservation in forest riparian. Regarding the environmental parameters, we found that AGR basins have higher turbidity, electrical conductivity, in the water and sand bed substrate. While FLO watershed are significantly different for water transparency and clayey substrates. Regarding the ichthyofauna, 70.705 individuals of eight orders, 22 families and 96 species were sampled, 56.55% of the species recorded in AGR and 43.45% in FLO. Despite the wide impact promoted by anthropic actions, we did not find significant differences for richness, diversity and equitability related to land use in the AGR and FLO watershed. We verified that some fish species were more associated to FLO watershed, while others species less sensitive to the AGR watershed. In this scenario, we recommend that monitoring be done to know and size the impacts of the degradation of ZRs and the effects over time to protect and preserve fish species with high endemism.